Partial replacement of corn with glycerin: digestibility and ruminal fermentation kinetics by in vitro gas production - Peripolli, Vanessa; Prates Ênio R; Barcellos Júlio OJ; Costa Jr João Batista G; Lopes Rúbia B; Camargo, Claudia M (Revista Colombiana de Ciencias Pecuarias, 2016)
glycerin, a co-product of biodiesel production, could be included in animal feeds. Objective: to evaluate the effects of partial replacement of corn with glycerin on digestibility and ruminal fermentation kinetics, estimated by the in vitro gas production technique. Methods: dietary treatments consisted of corn substitution with crude glycerin (0, 4, 8, and 12% on a dry matter basis). In vitro digestibility of neutral detergent fiber and organic matter were calculated as the difference between the amount of incubated and undigested substrate. Cumulative gas pressure was measured in vitro using automatic equipment. Gas production kinetics was analyzed using a dual-pool logistic model. Results: increasing levels of crude glycerin to replace corn did not affect in vitro digestibility of neutral detergent fiber, organic matter, ammonia nitrogen content, or degradation rates. A negative linear effect on the partitioning factor and a linear increase in the rapidly degradable fraction were observed with the inclusion of crude glycerin. Conclusions: dietary inclusion of up to 12% crude glycerin (dry matter basis) replacing corn did not affect diet digestibility. A greater volume of gas was observed with the highest inclusion level of glycerin, indicating that alfalfa hay, corn and crude glycerin combination could affect fermentation, suggesting the occurrence of associative effects.